2010
DOI: 10.3109/01421591003686237
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship for the physician recruited from abroad to Canada for rural practice

Abstract: Background: Mentoring is one way to help physicians new to a country assimilate. Aim: This study examined the feasibility and focus of a mentoring program from the perspective of medical leaders (leaders) and physicians new to Canada ( physicians). Methods: Focus groups with 23 physicians were held in six regional centers. Face-to-face interviews were held with 10 leaders. They were asked to discuss how a mentoring program might be helpful and how a program might be designed and evaluated. Results: Both leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 10 publications
(17 reference statements)
2
15
0
Order By: Relevance
“…International studies that have investigated the organisation of mentoring schemes for foreign doctors recommend preparation of a detailed description of the mentor's role and tasks, as well as thorough training of those who assume this role (9). Similar recommendations were made by the informants in our study, and the findings therefore concur well with those made by other studies.…”
Section: Views On a Mentoring Scheme And How It Should Be Organisedsupporting
confidence: 82%
See 2 more Smart Citations
“…International studies that have investigated the organisation of mentoring schemes for foreign doctors recommend preparation of a detailed description of the mentor's role and tasks, as well as thorough training of those who assume this role (9). Similar recommendations were made by the informants in our study, and the findings therefore concur well with those made by other studies.…”
Section: Views On a Mentoring Scheme And How It Should Be Organisedsupporting
confidence: 82%
“…This accords with recommendations made in some international studies (9). The problem inherent in such a voluntary scheme is that it may fail to capture all those who have a need for it.…”
Section: Views On a Mentoring Scheme And How It Should Be Organisedsupporting
confidence: 58%
See 1 more Smart Citation
“…7 Papers described engagement in mentoring as leading to accomplishment in the form of personal development. Of the small number of studies describing specific aspects of personal development, mentoring was reported as leading to improved confidence, 22,23,25 increased energy levels 23 and better stress management, 22,25 as well as helping mentees grow socially, 26 emotionally, 26,27 and intellectually. 27 One study proposed three broad areas of benefit, and underlying processes that overlapped in mentoring;…”
Section: Better Physical and Psychological Healthmentioning
confidence: 99%
“…21,22,27,30,31 Mentoring schemes also supported career progression and professional development of mentees, in the identification and discussion of career decisions, 22,25,30,31 the identification and completion of career goals 22,25 and through transference of expert knowledge from mentor to mentee. 26,27,29 Better work-life balance was described as a useful outcome for mentees 17,22,24,28 with mentoring identified as helping mentees manage workload, including work-life balance. 25, 32 Banini 32 asserted that mentors have a responsibility to 'take an active role in mentoring the younger generation' in helping mentees achieve work-life balance.…”
Section: 25mentioning
confidence: 99%